Toward measuring the usability of decision support applications in fog computing environment - Oras Abdulkhdhur Hussein; Ayad Hameed Mousa (Indonesian Journal of Electrical Engineering and Computer Science, 2023)
Decision support systems are applications that provide meaningful information and help with decision support. To gain the benefits of these applications, they need to be used optimally. Thus, the optimal manner to utilize relies on several properties, such as usability. This research aims to investigate the decision support systems applications (DSS) in terms of usability evaluation and propose a usability instrument for DSS in a fog computing environment. Recently, complexity is a major problem with most software products. Hence, the way to ensure user satisfaction is by measuring its usability. The study is based on the research question: What dimensions and their elements that utilize to evaluate the usability of DSS applications. A systematic literature review (SLR) was conducted to understand and extract all the instrument’s dimensions and elements. To confirm the validity of the proposed instrument, Multi scientific methods were adapted such as face validity, a pilot study for testing the goodness of proposed instrument consistency, and factor analysis. Furthermore, Bartlett’s test was utilized to ensure the reliability of the developed instrument. Eventually, the validated instrument was used to evaluate DSS application in a fog computing environment. The findings show that the proposed instrument is workable in practice.